2023
DOI: 10.1057/s41599-023-01871-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the factors affecting ICT integration of in-service teachers in Henan Province, China: structural equation modeling

Abstract: The integration of Information and Communication Technology (ICT) can significantly improve teaching and learning outcomes, but various factors determine the degree to which ICT is integrated into educational practices. This study used quantitative methodology to examine four key factors that impact in-service teachers’ ICT integration and how they interact with each other. Data was collected through snowball sampling from 685 in-service teachers in Henan Province, China. Using partial least squares structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
0
0
Order By: Relevance
“…A research study was conducted in Henan Province, China, with the aim of examining the various factors that influence the integration ICT among in-service teachers. The findings of this study offer valuable insights that may also be applicable to pre-service teachers (Peng et al, 2023). The research revealed that there are various crucial elements that influence the integration of ICT by teachers, as well as their interactions.…”
Section: Information and Communication Technology Competenciesmentioning
confidence: 80%
“…A research study was conducted in Henan Province, China, with the aim of examining the various factors that influence the integration ICT among in-service teachers. The findings of this study offer valuable insights that may also be applicable to pre-service teachers (Peng et al, 2023). The research revealed that there are various crucial elements that influence the integration of ICT by teachers, as well as their interactions.…”
Section: Information and Communication Technology Competenciesmentioning
confidence: 80%
“…Takođe važno je naglasiti da polne razlike u mnogim istraživanjima nisu direktno ispitivane, jer na tom uzorku često imamo neravnomerno raspoređen uzorak, odnosno situaciju u kojoj imamo značajno veće prisustvo ispitanica u odnosu na ispitanike, što u ovom istraživanju nije bio slučaj. Pojedini autori su analizirajući percepciju prosvetnih radnika prema učenicima sa IO govorili o tome da su nastavnice u svom radu veoma često neformalnije, podržavajuće, izražajnije i više usmerene na rad sa ovim učenicima, te samim tim iz tog razloga češće pronalaze načine da im pomognu u školskom okruženju, tako da se korišćenje raznih proizvoda IKT navode kao nešto što u tom procesu najčešće koriste (Nasser & Sahari, 2012;Wood, 2012), dok novi podaci iz literature potvrđuju da one primenjuju ovu vrstu tehnologije u svojim učionicama mnogo češće u odnosu na nastavnike (Peng et al, 2023).…”
Section: Diskusijaunclassified